Public Expenditure Review Summary : Social Assistance Program and Public Expenditure Review 1 - World Bank (World Bank, Jakarta, 2017)
Public expenditure on household-based social assistance (SA) in Indonesia has increased significantly since 2005. From a low base in the early 2000s, Indonesia's aggregate national public expenditures on SA permanently increased from 2005 after the central government allocated a portion of the savings from fuel subsidy reforms to a number of SA initiatives. In 2010, national expenditures on SA are estimated at Rp 29,709 billion (US$ 3.3 billion), equivalent to 2.6 percent of total national expenditures and 0.5 percent of gross domestic product (GDP). Indonesia's strong fiscal position leaves Indonesia well placed to further increase SA expenditures. Declining debt payments and subsidy reductions have opened up fiscal space over the past decade and supported a general increase in social sector and SA spending. With debt-to-GDP of just 25 percent in 2010, Indonesia could further increase expenditure on both items without raising debt levels. Nonetheless, current expenditures on SA are dwarfed by spending on regressive energy subsidies which in some years consume over 20 percent of total national expenditures. The increase in spending after 2005 primarily reflects greater central government investment in programs to protect poor households from fuel and food shocks as well as large health and education expenses. The central government is the dominant player in the SA sector, accounting for almost 90 percent of total expenditures. In years when the government has increased regulated fuel prices (2005-06 and 2008-09), the largest compensatory SA response has been an unconditional cash transfer program (BLT) to vulnerable households to help cushion them from the inflationary shock.